The ABC of APC. - Fearnhead, N; Britton, M; Bodmer, W (2001)
Familial adenomatous polyposis (FAP) is an autosomal dominant inherited disease characterized by the presence of adenomatous polyps in the colon and rectum, with inevitable development of colorectal cancer if left untreated. FAP is caused by germline mutations in the adenomatous polyposis coli (APC) gene. Somatic mutations in the APC gene are an early event in colorectal tumorigenesis, and can be detected in the majority of colorectal tumours. The APC gene encodes a large protein with multiple cellular functions and interactions, including roles in signal transduction in the wnt-signalling pathway, mediation of intercellular adhesion, stabilization of the cytoskeleton and possibly regulation of the cell cycle and apoptosis. The fact that APC is an integral part of so many different pathways makes it an ideal target for mutation in carcinogenesis. This review deals with our understanding to date of how mutations in the APC gene translate into changes at the protein level, which in turn contribute to the role of APC in tumorigenesis.